Transparency Without Resonance: Litigation Risk Disclosure and Market Apathy in Indonesia’s Capital Market - Yusuf, Chandra (Research of Business and Management, 2025)
This study examines the gap between litigation risk disclosure and market responsiveness in Indonesia's capital markets. Although Law No. 8 of 1995 and POJK No. 29/POJK.04/2016 require issuers to disclose material legal risks, findings show such announcements rarely affect stock prices or investor behavior. Using a mixed normative–empirical method, the research combines legal analysis with simulated event studies and content analysis of disclosures from five issuers between 2020 and 2024. Results indicate most disclosures are vague and non-quantitative, omitting claim values, probability of loss, or operational impacts, thereby weakening informational value and salience. Event study results reveal no significant abnormal returns in a ±5-day window around disclosure dates, challenging the Efficient Market Hypothesis (EMH). To explain these outcomes, the study employs EMH, signaling theory, salience theory, and legal materiality, explaining why transparency fails to drive reactions. Contributing factors include the absence of binding standards, under-disclosure to avoid reputational harm, and weak investor literacy. Recommendations include standardized disclosure formats, quantification, stronger audits, and enhanced investor education. By framing transparency as both a legal and behavioral issue, the study proposes a framework to strengthen the credibility and effectiveness of litigation risk communication in emerging markets.